2010
DOI: 10.2147/opth.s14257
|View full text |Cite
|
Sign up to set email alerts
|

Spectral domain optical coherence tomography as an effective screening test for hydroxychloroquine retinopathy (the “flying saucer” sign)

Abstract: PurposeWhile the long-term incidence of hydroxychloroquine (HCQ) retinopathy is low, there remains no definitive clinical screening test to recognize HCQ toxicity before ophthalmoscopic fundus changes or visual symptoms. Patients receiving HCQ were evaluated with spectral domain optical coherence tomography (SD OCT) to assess the feasibility of identifying HCQ retinopathy at an early stage.MethodsTwenty-five patients referred for the evaluation of hydroxychloroquine toxicity underwent a comprehensive ocular ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 25 publications
5
88
0
8
Order By: Relevance
“…13 With advanced retinopathy, anatomical changes including perifoveal loss of the inner segment-outer segment junction of the photoreceptors, outer retinal thinning, and posterior displacement of the inner retina toward the RPE have been reported, which are indicative of a severe level of toxicity. 14,15 Similar patterns of Plaquenil toxicity have been described using ultra-high-resolution OCT. 16 These SD-OCT features, however, are seen largely in patients with paracentral scotomas or advanced maculopathy on HVF. None of our patients had these abnormalities.…”
Section: Discussionmentioning
confidence: 70%
“…13 With advanced retinopathy, anatomical changes including perifoveal loss of the inner segment-outer segment junction of the photoreceptors, outer retinal thinning, and posterior displacement of the inner retina toward the RPE have been reported, which are indicative of a severe level of toxicity. 14,15 Similar patterns of Plaquenil toxicity have been described using ultra-high-resolution OCT. 16 These SD-OCT features, however, are seen largely in patients with paracentral scotomas or advanced maculopathy on HVF. None of our patients had these abnormalities.…”
Section: Discussionmentioning
confidence: 70%
“…6,11,[20][21][22] Majority of the previous studies were related to the pathologies associated with the outer retinal segment involving retinal pigment epithelium and photoreceptors. 13,21,23 However, some other studies also demonstrated HCQassociated damage in the inner retinal segment. 11,19 In our study, we also found statistically significant thinning of RGC-IPL, which is a part of the inner retina; average RGC-IPL thickness, and all segments except inferior segment in the group of patients who were taking HCQ compared to the controls who were not taking the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence about the usefulness of FAF in early diagnosis is lacking. 18,19 Macular perimetry, funduscopic examination and photography continue to provide the highest yields of early cases. 17 It has been recently considered that revised guidelines, 4 emphasizing mfERG, SD-OCT or FAF, raised screening cost without improving case detection.…”
Section: Discussionmentioning
confidence: 99%